Forest management affects ecosystem functioning (predation and herbivory) but not ecosystem constancy - (:unkn) unknown (Elsevier BV, 2024)
Forest management can affect both the functioning and stability of ecosystems. Constancy and persistence are key factors that contribute to the overall stability of an ecosystem. These factors can be highly variable and change across forest ecosystems. W...
Keywords: Manejo forestal; Ecosistemas